PENGARUH PELATIHAN TERHADAP KINERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI PADA KARYAWAN PT. X - Citra Neza; Harif Amali Rivai (Journal of Management and Business Review, 2020)
This study aims to determine the effect of training on job performance. The effect of work motivation as a mediating variable was also examined. The research was conducted on employees of PT. X. The data gathered from  186 people permanent employees of PT. X. The data was collected through a field survey. The result of the data from survey was analyzed using SmartPLS software. And the result supported that training significantly positive effect on employee job performance. Employee motivation was forming significantly effect on employee job performance. The result of the study was also supported that’s training significantly positive impact on motivation. The study concludes that employee motivation partially mediated the relationship between employee training and employee job performance.